Proposed Solution for Stony Debris-Flow Control Works in Two Headwater Basins with Morphological Changes - Mauro Boreggio; Matteo Barbini; Martino Bernard; Massimo Degetto; Carlo Gregoretti (GeoHazards)
Stony debris flows originating from the two basins of Jaron di Sacomedan and Jaron dei Ross pose a significant threat to the inhabited area of Chiapuzza (Dolomites, Northeastern Italian Alps) and the national road SS 51. In the upper part of the Jaron dei Ross basin, a large scree at the foot of a rocky amphitheater undergoes morphological changes due to frequent rockfalls. Previous mitigation efforts have proven inadequate, and after identifying the causes of their failure, new control measures are being planned. These works aim to direct debris flows towards a deposition area capable of intercepting flows from both the Jaron dei Ross and Jaron di Sacomedan basins. Essentially, the upper works in the Jaron dei Ross basin divert debris flows away from the populated area and channel them to a location where the sediment volume transported by debris flows from both basins can be stored. This solution is designed to protect both the Chiapuzza community and the SS51 national road.